Nematode diversity in tomato and cucumber agroecosystems of Fergana Valley and control of root-knot nematodes, Uzbekistan - SARDORBEK KAMBAROV; FARKHOD TO’XTASINOV; ABDUMUKHTAR YAKHYOYEV; KHOLISA ESHOVA; FAYZULLA KHABIBULLAEV; KHURSHIDJON MAMUROV; KHALIMJON QORABOYEV; SAYYORA ABDUQAYUMOVA (Society for Indonesian Biodiversity, 2026)
Abstract. Kambarov S, To’xtasinov F, Yakhyoyev A, Eshova K, Khabibullaev F, Mamurov K, Qoraboyev K, Abduqayumova S. 2026. Nematode diversity in tomato and cucumber agroecosystems of Fergana Valley and control of root-knot nematodes, Uzbekistan. Biodiversitas 27 (2): d270235. https://doi.org/10.13057/biodiv/d270235. Plant-parasitic nematodes, particularly root-knot nematodes (Meloidogyne spp.), cause substantial yield losses in vegetable crops and threaten the sustainability of agroecosystems. This study assessed nematode diversity in tomato (Solanum lycopersicum) and cucumber (Cucumis sativus) agroecosystems of the Fergana Valley (Uzbekistan) and evaluated the field efficacy of the nematicides Nematorin (fosthiazate) and Nematozin (mebendazole) during the 2025 growing season. Nematodes were extracted using modified Baermann and flotation techniques and identified based on morphological characters. In total, 60 nematode species belonging to 22 genera, 11 families, and 5 orders were recorded, with soil showing the highest diversity (S: 20, H′: 2.706, 1-D: 0.916), followed by roots (S: 9, H′: 1.779) and the stem-leaf compartment (S: 4, H′: 1.257). Bacterivorous nematodes were the dominant trophic group. Both nematicides significantly reduced the density of invasive second-stage juveniles (J2) and root galling compared with the untreated control (p<0.001). Nematozin achieved 90.1% and 90.4% biological efficacy in tomato and cucumber, respectively, whereas Nematorin reached 85.7% and 87.9%. These reductions were accompanied by yield increases from 6.5 t ha⁻¹ in the control to 10.8 t ha⁻¹ (Nematozin) and 8.7 t ha⁻¹ (Nematorin) in tomato, and to 10.2 t ha⁻¹ in treated cucumber plots. Identification of Meloidogyne was based on morphological criteria; therefore, species-level resolution remains limited and future studies should incorporate molecular markers for confirmation. Overall, integrating nematode community assessment with chemical control measures can contribute to improved management of root-knot nematodes in vegetable agroecosystems of the Fergana Valley.